2018
DOI: 10.1182/blood-2017-07-795757
|View full text |Cite
|
Sign up to set email alerts
|

NR4A1 and NR4A3 restrict HSC proliferation via reciprocal regulation of C/EBPα and inflammatory signaling

Abstract: Members of the NR4A subfamily of nuclear receptors have complex, overlapping roles during hematopoietic cell development and also function as tumor suppressors of hematologic malignancies. We previously identified NR4A1 and NR4A3 (NR4A1/3) as functionally redundant suppressors of acute myeloid leukemia (AML) development. However, their role in hematopoietic stem cell (HSC) homeostasis remains to be disclosed. Using a conditional / knockout mouse (CDKO), we show that codepletion of NR4A1/3 promotes acute change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 67 publications
(75 reference statements)
5
49
1
Order By: Relevance
“…One of the proteins whose abundance was upregulated by dexamethasone in PB-derived CFU-Es, but not CB-derived CFU-Es, was NR4A1 ( Figure 3, C and D), a negative cell-cycle regulator. NR4A1 is an interesting target, given its role as a regulator of the cell cycle (22) and of T cell differentiation (33). NR4A1 also binds to HIF1α (34), an important regulator of erythroid differentiation (35).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the proteins whose abundance was upregulated by dexamethasone in PB-derived CFU-Es, but not CB-derived CFU-Es, was NR4A1 ( Figure 3, C and D), a negative cell-cycle regulator. NR4A1 is an interesting target, given its role as a regulator of the cell cycle (22) and of T cell differentiation (33). NR4A1 also binds to HIF1α (34), an important regulator of erythroid differentiation (35).…”
Section: Resultsmentioning
confidence: 99%
“…Dexamethasone did not affect BFU-Es, but using a new set of cell-surface markers, we identified a unique, PB progenitor-generated subset of transitional CD34 + CD36 + CD71 hi CD105 med CFU-Es that were dexamethasone responsive. Mass spectrometry-based quantitative proteomics analyses revealed substantial differences in the effects of dexamethasone on PB and CB progenitors, with upregulation of nuclear receptor subfamily 4 group A member 1 (NR4A1), a negative cell-cycle regulator (22), in the former cell type. Furthermore, we found that the p57 Kip2 Cip/Kip CKI was specifically upregulated by dexamethasone in PB-derived CFU-Es and that its downregulation significantly attenuated the effects of this glucocorticoid.…”
Section: Introductionmentioning
confidence: 99%
“…Nr4a1, Gata2, Junb , and Btg2 as up‐regulated genes in dKO mice may also contribute to the decelerated cell cycle of HSCs. Nr4a1 and Nr4a2 are preferentially expressed in HSCs and control HSC quiescence by acting upstream of key HSC transcriptional networks (42). GATA2 is essential for HSC survival (43).…”
Section: Discussionmentioning
confidence: 99%
“…Cells were then washed and either stored at 4 o C or resuspended in SM containing 2 µg/ml DAPI and analyzed on a BD LSRII analyzer equipped with a UV laser (Becton-Dickenson). Myc staining was performed as previously described (Freire and Conneely, 2018). 10 7 BM cells were stained for 30 minutes on ice with SM containing the following antibodies: PE-Cy5-conjugated anti-CD3, CD4, CD5, CD8, Gr-1 and Ter119 as a lineage exclusion stain, Flk2biotin, CD34-FITC, EPCR-PE, Mac-1-PE/Cy7, CD48-A700, and cKit-APC/Cy7, washed in SM and stained for 30 min in 1:4 Brilliant buffer:SM containing Sca-1-BV421, SA-BV605 and CD150-BV785.…”
Section: Methodsmentioning
confidence: 99%